Titanium as a Beneficial Element for Crop Production - Lyu, Shiheng; Wei, Xiangying; Chen, Jianjun; Wang, Cun; Wang, Xiaoming; Pan, Dongming (Frontiers in Plant Science, 2017)
Titanium (Ti) is considered a beneficial element for plant growth. Ti applied via roots or leaves at low concentrations has been documented to improve crop performance through stimulating the activity of certain enzymes, enhancing chlorophyll content and photosynthesis, promoting nutrient uptake, strengthening stress tolerance, and improving crop yield and quality. Commercial fertilizers containing Ti, such as Tytanit and Mg-Titanit, have been used as biostimulants for improving crop production; however, mechanisms underlying the beneficial effects still remain unclear. In this article, we propose that the beneficial roles Ti plays in plants lie in its interaction with other nutrient elements primarily iron (Fe). Fe and Ti have synergistic and antagonistic relationships. When plants experience Fe deficiency, Ti helps induce the expression of genes related to Fe acquisition, thereby enhancing Fe uptake and utilization and subsequently improving plant growth. Plants may have proteins that either specifically or nonspecifically bind with Ti. When Ti concentration is high in plants, Ti competes with Fe for ligands or proteins. The competition could be severe, resulting in Ti phytotoxicity. As a result, the beneficial effects of Ti become more pronounced during the time when plants experience low or deficient Fe supply.